Medieval Intrigue : Royal Murder and Regnal Legitimacy. - Mortimer, Ian (Bloomsbury Publishing PLC, 2010)
Ian Mortimer examines some of the most controversial questions in medieval history, outlining his ground-breaking approach to historical evidence. An important work from one of today's most original and popular medieval historians.